О межэтнических противоречиях в Римской империи в период кризиса ІІІ века - Сергеев, И.П. (My University, 2004)
J. Sergeev. On Interethnical Contradictions in the Roman Empire During the Crisis of the III Century The article is devoted to the struggle between Illyrians and Syrians for the political power in the Roman Empire. The author analyses the importance of interethnical contradictions in the development of the provincial separatism in the Roman Empire during the crisis of the III century. The conclusion that sharpening of interethnical contradictions in the Roman Empire during the crisis of the III century was not very important is made in the article. But it is necessary to explain these contradictions with clarification of the questions of the separatism of provinces and of the scale of departure of the Empire's underclasses.